PETROGRAPHIC, FLUID INCLUSION AND OXYGEN ISOTOPE CHARACTERISTICS OF RAMAND AREA, NW IRAN - Bootorabi, Sima; Mehrnia, Reza; Khakzad, Ahmad; Nezafati, Nima (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.1047, 2020)
Ramand mineralization area is located at a distance of about 60 km from the provincial capital of Qazvin province, Iran. The studied area is a part of the Central Iran structural zone in the southern part of Danesfahan geological map. Lithological units in Ramand area are composed of riodacite, rhyolite, tuff riodacite, crystal tuff and riodacite. The presence of clay minerals indicates argillic alteration, which is a good indicator of mineralization. This type of alteration can be detected in volcanic regions which have been severely affected by argillic alteration. Silicification is the most important evidence of precious metal potential in post magmatic environments. According to mineralogical studies, sulfide minerals in the area consist of pyrite and chalcopyrite with supergene minerals such as covellite, malachite, and Fe hydroxides. Based on phase content, the three types of inclusion in Ramand area include vapor, vapor liquid, and liquid rich inclusions. According to fluid inclusion data, the liquid vapor homogenization temperature [ T H (L–V) ] varied from 73 to 307 °C, and salinity ranged from 1.75 to 4.74 wt% NaCl eq. The calculated δ18O values of water in equilibrium with quartz ranged from 5.8 to 6.9 per ml. Calculated δ18O values of water in equilibrium with calcite ranged from 4.4 to 9.4 per ml. These data suggest that the ores formed most likely originated from magmatic hydrothermal sources along with some meteoric solutions during mineralization processes.